Financial integration in autocracies: Greasing the wheel or more to steal? - Ramin Dadasov; Philipp Harms; Oliver Lorz (Philipps-University Marburg, Faculty of Business Administration and Economics, 2010)
This paper analyzes the influence of financial integration on institutional quality. We construct a dynamic political-economic model of an autocracy in which a ruling elite uses its political power to expropriate the general population. Although financial integration reduces capital costs for entrepreneurs and thereby raises gross incomes in the private sector, the elite may counteract this effect by increasing the level of expropriation. Since de facto political power is linked to economic resources, financial integration also has long-run consequences for the distribution of power and for the rise of an entrepreneurial class.
Keywords: F21; O16; P48; 330; institutions; capital mobility; political economy; Kapitalmarktliberalisierung; Kapitalmobilität; Macht; Autoritäres System; Public Choice; Theorie